Pembelajaran Demonstrasi di Pendidikan Keagamaan Buddha - Mariana Lestari; Sutiyono Sutiyono; Priono Priono; Susanto Susanto (STAB Maitreyawira, 2024)
The demonstrative approach to enhance student learning outcomes is covered in this study. Presenting teachings to pupils by showing them a specific procedure, circumstance, or item whether authentic or merely an imitation is known as the disclosure approach. Demonstrations as a presentation technique are inextricably linked to the teacher's spoken explanations. Demonstrations can offer more tangible learning materials, even though the role of the students is the only thing that needs to be taken into account. Demonstrations can be utilized to help expository and inquiry tactics succeed in approach learning. The goal of this study is to improve scientific learning activities and results for students in the classroom. This study employs a literature study methodology and is qualitative in nature. The study's findings, which have been published in a number of theses and journals, demonstrate that the demonstration technique can enhance student learning outcomes.